Impacto de la pandemia de Covid-19 en el consumo de medios en España. - Blasco, Mireia Montaña; Castellà, Candela Ollé; Raso, Montse Lavilla (Revista Latina de Comunicación Social, 2020)
Introduction: This study aims to explore the impact of the Covid-19 pandemic on media habits and consumption in Spain, one of the most severely affected countries. Methodology: A representative online survey of the Spanish population (N = 1,500 participants) was conducted from March 13 to 30, 2020, coinciding with the first weeks of home confinement. The sample was studied according to two variables, gender (Women N = 750; Men N = 750) and age (18-39 years individuals, N = 720; over 40 years individuals N = 780) to detect the most relevant specificities of each group. The sampling error is ± 4.38% to 95% confidence. Results: Results highlight that television is the most used media when it comes to finding out about the virus, before digital media. It should be noted that infoshow-type television programs manage to accumulate more audience than the traditional news programs. The least used media to get information about the evolution of the Covid-19 are Internet, social networks, radio, information by relatives or acquaintances, and traditional press. Although radio consumption seems not to be significant to stay informed, this medium is the most credible, in addition to television. Finally, the consumption of over-the-top (OTT) platforms has grown considerably during this period. Discussion: Television recovers the audience of the youngest targets that it seemed to have lost in in favor of digital media. Conclusions: An increasingly complex and competitive media landscape is consolidating.